Discursive strategies of Chinese elders in intergenerational conflicts: A critical discourse analysis of mediation television programs in China - Chen Cai; Heng Hu (PLoS ONE, 2025)
Research on conflict discourse highlights the value of a cross-cultural perspective and the need to explore its features across different cultural contexts. However, there is limited research on conflict discourse among Chinese elders, particularly within the framework of building an Age-Friendly Society. To address this gap, this study adopts Fairclough’s dialectical-relational approach in critical discourse analysis to examine the strategies Chinese elders employ in intergenerational conflicts. Drawing on Li’s framework of conflict strategies—competition, cooperation, avoidance, and compromise—this study identifies how Chinese elders use discourse to safeguard their rights and foster mutual understanding within family interactions. The findings reveal that these four strategies serve as discursive means for elders to achieve self-fulfillment, protect their rights, and sustain family harmony amidst social change. This study offers a systematic analysis of conflict resolution strategies in intergenerational discourse, highlighting the nuanced equilibrium that elders navigate between upholding traditional values and accommodating the evolving dynamics of contemporary family life.